Examining the immune signatures of SARS-CoV-2 infection in pregnancy and the impact on neurodevelopment: Protocol of the SIGNATURE longitudinal study - Garrido-Torres, Nathalia; Cerrillos, Lucas; García Cerro, Susana; Pérez Gómez, Alberto; Canal-Rivero, Manuel; de Felipe, Beatriz; Alameda, Luis; Marqués Rodríguez, Renata; Anillo, Sergio; Praena, Julia; Duque Sánchez, Cristina; Roca, Cristina; et al. (Frontiers in Pediatrics, 2022)
The COVID-19 pandemic represents a valuable opportunity to carry out cohort studies that allow us to advance our knowledge on pathophysiological mechanisms of neuropsychiatric diseases. The enormous scientific effort along with the current availability of sophisticated biological techniques and evaluation procedures represent a unique option for this purpose. One of these opportunities is the study of the relationships between inflammation, brain development and an increased risk of suffering from neuropsychiatric disorders. Based on the hypothesis that neuroinflammation during early stages of life is associated with neurodevelopmental disorders and confers a greater risk of developing neuropsychiatric disorders, we propose a cohort study of SARS-CoV-2-infected pregnant women and their newborns. The main objective of SIGNATURE project is to explore how the presence of prenatal SARS-CoV-2 infection and other non-infectious stressors (lockdowns, stressful life events related with work and home and other) generates an abnormal inflammatory activity in the newborn. The cohort of women during the COVID-19 pandemic and will be psychological and biological monitored during their pregnancy, delivery, childbirth and postpartum. The biological information of the umbilical cord (foetus blood) and peripheral blood from the mother will be obtained after childbirth. These samples and the clinical characterisation of the cohort of mothers and newborns, of which we will be able to do an exhaustive longitudinal follow-up, are tremendously valuable at this time. There is a need to establish new research strategies to understand the pathophysiology of neuropsychiatric diseases and to discover new molecular and cellular mechanisms involved in the development of the central nervous system.